2009
DOI: 10.1002/cbf.1536
|View full text |Cite
|
Sign up to set email alerts
|

I405V and TaqIB polymorphisms of the cholesteryl ester transfer protein and their relation to serum lipid and lipoprotein levels in a Turkish population

Abstract: Cholesteryl ester transfer protein (CETP) plays a central role in high-density lipoprotein (HDL) metabolism. Genetic polymorphisms of the CETP gene can influence levels of serum lipoproteins. It has been reported that mean HDL-cholesterol (HDL-C) concentrations are low in Turkish population. Thus, we investigated the frequencies of the common I405V and TaqIB polymorphisms of the CETP gene and their relation to serum lipid and lipoprotein levels in a Turkish population. The variant allele frequencies of I405V a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…, 2005). However, in two other studies from Turkey, the TaqIB polymorphism was not associated with HDL-C level or risk of CAD among angiographically documented patients with CAD (Tanrikulu-Kucuk et al, 2010) and was not correlated to HDL-C in healthy individuals (Dogru-Abbasog et al, 2009). Also, Chaaba et al (2005) reported no association between TaqIB polymorphism and CAD in T2DM.…”
mentioning
confidence: 95%
“…, 2005). However, in two other studies from Turkey, the TaqIB polymorphism was not associated with HDL-C level or risk of CAD among angiographically documented patients with CAD (Tanrikulu-Kucuk et al, 2010) and was not correlated to HDL-C in healthy individuals (Dogru-Abbasog et al, 2009). Also, Chaaba et al (2005) reported no association between TaqIB polymorphism and CAD in T2DM.…”
mentioning
confidence: 95%